PENGEMBANGAN PERTANIAN PERKOTAAN STUDI KASUS: PETERNAKAN PERKOTAAN DI KOTA SINGKAWANG - KURNIAWAN, ABDUL HARIS ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Urban farming is a potential economic activities because of increasing demand for urban farm products for urban population. This research aimed to document urban farming practices in Singkawang Municipality, and to study factors influencing such activities. This was an exploratory research using qualitative descriptive approach. Data were collected from field observations and interviews with respondents. Data were then classified into three types of farming businesses, including traditional, semicommercial, and commercial business types. The research shows that urban farming practices in Singkawang Municipality is increasing. It is indicated by increasingly number of livestock population and production. The semi-commercial and commercial farming are reliable business, and the margin produced is considered to sufficiently meet family needs. The farming business in Singkawang Municipality belong to conventional in type. The farming activities in Singkawang Municipality are productive business to perform as main or sideline business providing work opportunity, and increasing incomes. The farming activities in Singkawang Municipality are influenced by two factors, namely internal factors involving physical or environmental aspects, farming business actors, and the government role, while external factors consisting of environmental effects (avian flu), strategic position, transportation and communication as well as supervising and elucidation. Internal factors supporting farming activities in Singkawang Municipality involve water resources and its availability, land, age and education level of business actors, knowledge and skills, technology, business experience, worker, government policy, strategic position, and transportation networks. While the supporting factors involve employment status, business motivation, capital, government programs, facilities and infrastructure supporting farming activities, budget and avian flu as well as supervision and elucidation. The research recommends that farmers needs to consider ...